Study of anatomical variations of mental foramen in dry adult human mandible - Acharya, Sunita; Mehta, Rupali; Kattimuthu, Prabhakaran Pearl (International Journal of Research in Medical Sciences, 2020)
Background: Mandible also known as the largest and inferior, primary facial bone of the face giving a curved shape to it. It changes its shape and gives variations to the bony structure of the face from birth till older age. Mental foramen is known as the ventage of the mandible and is an important mark of the face for carrying out many diagnostics and surgical processes along with anesthetic procedures of the face. Thus, the present study is designed with an aim to get insight knowledge of position and shape of mental foramen in dry adult human mandible. Methods: Totally, 60 bones were studied in 2 years duration. The study was carried out in the Department of Anatomy of Geetanjali Medical College and Hospital and Rabindranath Medical College. The position of mental foramen was studied using an instrument known as digital Vernier Calliper (in mm) while shape was analyzed visually. Position of mental foramen was calculated using Statistical package for social sciences (SPSS) software. Results: The present study showed that the position of mental foramen from symphysis menti and posterior border of ramus of mandible was more from right side than left side and found to be insignificant while position of mental foramen from inferior border of body of mandible was more from left side than right side and found to be insignificant for right side while significant for left side. The shape of mental foramen from right side was found to be (Oval shape- 68.33% and round shape – 31.66%) while for left side was found to be (Oval shape- 71.66% and round shape – 28.33%). Conclusions: Hence, mental foramen plays a pivotal role in performing major facial surgeries and is an important landmark for several facial procedures performed.